Cinacalcet in patients with chronic kidney disease: a cumulative meta-analysis of randomized controlled trials. - Suetonia C Palmer; Ionut Nistor; Jonathan C Craig; Fabio Pellegrini; Piergiorgio Messa; Marcello Tonelli; Adrian Covic; Giovanni F M Strippoli (PLoS Medicine, 2013)
Background Calcimimetic agents lower serum parathyroid hormone levels in people with chronic kidney disease (CKD), but treatment effects on patient-relevant outcomes are uncertain. We conducted a systematic review and meta-analysis to summarize the benefits and harms of calcimimetic therapy in adults with CKD and used cumulative meta-analysis to identify how evidence for calcimimetic treatment has developed in this clinical setting. Methods and findings Cochrane and Embase databases (through February 7, 2013) were electronically searched to identify randomized trials evaluating effects of calcimimetic therapy on mortality and adverse events in adults with CKD. Two independent reviewers identified trials, extracted data, and assessed risk of bias. Eighteen trials comprising 7,446 participants compared cinacalcet plus conventional therapy with placebo or no treatment plus conventional therapy in adults with CKD. In moderate- to high-quality evidence (based on Grading of Recommendations Assessment, Development, and Evaluation criteria) in adults with CKD stage 5D (dialysis), cinacalcet had little or no effect on all-cause mortality (relative risk, 0.97 [95% confidence interval, 0.89-1.05]), had imprecise effect on cardiovascular mortality (0.67 [0.16-2.87]), and prevented parathyroidectomy (0.49 [0.40-0.59]) and hypercalcemia (0.23 [0.05-0.97]), but increased hypocalcemia (6.98 [5.10-9.53]), nausea (2.02 [1.45-2.81]), and vomiting (1.97 [1.73-2.24]). Data for clinical outcomes were sparse in adults with CKD stages 3-5. On average, treating 1,000 people with CKD stage 5D for 1 y had no effect on survival and prevented about three patients from experiencing parathyroidectomy, whilst 60 experienced hypocalcemia and 150 experienced nausea. Analyses were limited by insufficient data in CKD stages 3-5 and kidney transplant recipients. Conclusions Cinacalcet reduces the need for parathyroidectomy in patients with CKD stage 5D, but does not appear to improve all-cause or cardiovascular mortality. Additional trials in CKD stage 5D are unlikely to change our confidence in the treatment effects of cinacalcet in this population.